Analisis Faktor-faktor Yang Mempengaruhi Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Variabel Moderasi - Aryadita, Putriana Hadi; Hariyanto, Eko; Wahyuni, Sri; Fitriati, Azmi (Owner : Riset dan Jurnal Akuntansi, 2024)
Abstract In managing a company which is characterized by the welfare of shareholders so that it reflects the high value of the Company. This research was conducted to determine the value of companies in the infrastructure sector in the 2018-2022 period based on factors that influence company value. The factors taken in this research are profitability, company size and leverage as well as dividend policy which are used as moderating variables in the research. This research uses a quantitative approach, namely by looking at the relationship between independent variables and dependent variables as well as moderating variables on the objects studied. The data used in this research is secondary data in the form of financial reports accessed via the Indonesian Stock Exchange website. The population in this research is Infrastructure sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. This research uses a purposive sampling technique. The samples that can be studied are 109 company data samples. In processing data and drawing conclusions, researchers used the SPSS program or software. The results of this research show that profitability, company size and dividend policy have no effect on the value of infrastructure companies, while leverage has a positive effect on the value of infrastructure companies. The results in this study indicate that dividend policy is unable to moderate and strengthen the influence of profitability, company size and leverage on the value of infrastructure companies.